Health-resource use and quality of life in children with bronchiectasis: a multi-center pilot cohort study - Yolanda G. Lovie-Toon; Keith Grimwood; Catherine A. Byrnes; Vikas Goyal; Greta Busch; I. Brent Masters; Julie M. Marchant; Helen Buntain; Kerry-Ann F. O'Grady; Anne B. Chang (BMC, 2019)
Abstract Background Bronchiectasis in children is an important, but under-researched, chronic pulmonary disorder that has negative impacts on health-related quality of life. Despite this, it does not receive the same attention as other chronic pulmonary conditions in children such as cystic fibrosis. We measured health resource use and health-related quality of life over a 12-month period in children with bronchiectasis. Methods We undertook a prospective cohort study of 85 children aged < 18-years with high-resolution chest computed-tomography confirmed bronchiectasis undergoing management in three pediatric respiratory medical clinics in Darwin and Brisbane, Australia and Auckland, New Zealand. Children with cystic fibrosis or receiving cancer treatment were excluded. Data collected included the frequency of healthcare attendances (general practice, specialists, hospital and/or emergency departments, and other), medication use, work and school/childcare absences for parents/carers and children respectively, and both parent/carer and child reported quality of life and cough severity. Results Overall, 951 child-months of observation were completed for 85 children (median age 8.7-years, interquartile range 5.4-11.3). The mean (standard deviation) number of exacerbations was 3.3 (2.2) per child-year. Thirty of 264 (11.4%) exacerbation episodes required hospitalization. Healthcare attendance and antibiotic use rates were high (30 and 50 per 100 child-months of observation respectively). A carer took leave from work for 53/236 (22.5%) routine clinic visits. Absences from school/childcare due to bronchiectasis were 24.9 children per 100 child-months. Quality of life scores for both the parent/carer and child were highly-correlated with one another, remained stable over time and were negatively associated with cough severity. Conclusions Health resource use in this cohort of children is high, reflecting their severe disease burden. Studies are now needed to quantify the direct and societal costs of disease and to evaluate interventions that may reduce disease burden, particularly hospitalizations.